Exploring simultaneous allocation to mating effort, sperm production, and body growth in male guppies. (3rd June 2015) - Devigili, Alessandro; Doldán-Martelli, Victoria; Pilastro, Andrea
Lay Summary: Individuals can invest their resources in somatic or sexual ornaments, armaments, and ejaculate. But, as resources are limited, they cannot invest in all traits equally. As a consequence when the investment in 1 trait is increased a reduction in other traits is expected. To test this trade-off hypothesis, we stimulated guppy males to over-invest in sperm production and observed how they changed other investments. Our results suggest that enhanced sperm production made males less sexually vigorous. Abstract : In several species, males increase their mating and sperm investment in the presence of unfamiliar females, the so-called Coolidge effect. Such an elevated reproductive effort is expected to be associated with a decreased investment in other costly traits, such as somatic growth and maintenance. How precopulatory, postcopulatory, and somatic investments interact one with each other, however, has been rarely evaluated simultaneously. We used the guppy ( Poecilia reticulata ), a polyandrous livebearing fish with alternative male mating tactics, to compare these 3 investments between males whose encounter rate with unfamiliar females was experimentally maintained at either high (high mate encounter rate [HER]) or low rate (low mate encounter rate [LER]) for 4 months. At the end of this period, HER males showed an increased sperm production as compared with their LER counterparts. This increment was accompanied with a reduction in the time spent following the female and by a shift from costly courtship displays to gonopodial thrusting, a less expensive coercive mating tactic. This effect may indicate a trade-off between these 2 components of male reproductive investment or may reflect a change in male optimal reproductive strategy associated with different mate encounter rate. In contrast, body growth was positively correlated with the increase in sperm production, and did not differ between experimental groups. Collectively, these results suggest that males did not vary their overall reproductive investment in response to their encounter rate with unfamiliar females, but differed significantly in the amount of resources available individually.